Real-life X-files : investigating the paranormal - Nickell, Joe (University Press of Kentucky, 2001)
As a former private investigator and forensic writer, Joe Nickell has spent much of his career identifying forged documents, working undercover to infiltrate theft rings, and investigating questioned deaths. Now he turns his considerable investigative skill toward the paranormal, researching the most well-known and mysterious phenomena all over the world-spontaneous human combustion, UFO visitations, auras, electronic poltergeists, and many, many more-with an eye toward solving these mysteries rather than promoting or dismissing them. Real-Life X-Files: Investigating the Paranormal examines the.
Keywords: Parapsychology -- Case studies.; Curiosities and wonders.; Impostors and imposture.; Parapsychologie -- Études de cas.; Curiosités et merveilles.; BODY, MIND & SPIRIT -- Parapsychology -- General.; SOCIAL SCIENCE -- Conspiracy Theories.; Curiosities and wonders; Impostors and imposture; Parapsychology; Case studies